Investigation of extreme CO2 concentration events at an Alpine station with Lagrangian Particle Dispersion Models - Mirsada Cravero; Silvia Ferrarese; Francesco Apadula; Giulia Zazzeri; Matteo M. Musso; Silvia Trini Castelli (Atmospheric Pollution Research, 2026)

Associations of IL-17 and TGF-β1 with physical frailty in older adults - Chiara Ceolin; Marina De Rui; Giulia Musso; Silvia Sturani; Adele Ravelli; Cristina Simonato; Franz Villanova; Sabrina Pigozzo; Luca Busetto; Angelo Antonini; Eleonora Fiorenzato; Martina Montagnana; et al. (GeroScience, 2026)
Background Physical frailty is a prevalent geriatric syndrome associated with reduced physiological resilience and adverse outcomes. Beyond classical inflammaging, age-related changes in immune regulation and tissue repair may contribute to frailty pathophysiology. Biomarkers involved in adaptive immune responses and remodeling pathways, such as IL-17 and TGF-β1, may help characterize the inflammatory-regenerative milieu associated with frailty. We therefore investigated the association between circulating immune biomarkers and physical frailty severity in older adults. Methods In this cross-sectional analysis, 167 community-dwelling outpatients aged ≥ 65 years (mean age 75.2 ± 6.4 years; 54.5% women) were classified as robust, pre-frail, or frail according to a phenotype-based frailty score. Circulating levels of TGF-β1, IL-17, IL-6, TNF-α, IL-10, and IFN-γ were measured. Associations with frailty were assessed using ordinal logistic regression, quantile regression, and component-specific logistic models. Results IL-17 concentrations progressively declined with increasing frailty severity (median 9.24 ng/L in robust vs. 4.91 ng/L in frail participants; p = 0.004). In adjusted ordinal models, higher IL-17 levels were independently associated with lower frailty severity (OR = 0.62, 95% CI 0.46–0.84; p = 0.002), with each doubling of IL-17 corresponding to a 28% reduction in frailty odds. Conversely, higher TGF-β1 levels were independently associated with greater frailty severity (OR = 2.33, 95% CI 1.05–5.13; p = 0.036). IL-17 showed consistent associations with physical frailty domains, including slowness (adjusted OR = 0.57), and low physical performance (adjusted OR = 0.68). Similar associations were observed in exploratory analyses restricted to cognitively intact participants. However, formal interaction analyses did not support significant effect modification by cognitive status. In contrast, classical inflammatory markers (IL-6, TNF-α), as well as IFN-γ and IL-10, were not significantly associated with frailty across any of the models. Conclusions Physical frailty was associated with lower IL-17 and higher TGF-β1 levels, suggesting that immune-related pathways beyond classical systemic inflammation may be associated with physical frailty. Rather than reflecting overt systemic inflammation, these findings suggest that biological pathways involved in immune regulation and tissue remodeling may be associated with physical frailty. IL-17 and TGF-β1 may therefore represent potentially informative biomarkers for future investigations of the biological mechanisms underlying resilience and functional decline in aging. Trial registration Not applicable.

Hydro-mechanical behaviour of a cement–bentonite mixture along evaporation and water-uptake controlled paths - Guido Musso; Vincenzo Sergio Vespo; Giulia Guida; Gabriele Della Vecchia (Geomechanics for Energy and the Environment, 2023)